MEMPELAJARI GEJALA PERUBAHAN IKLIM MELALUI ANALISA DERET WAKTU CURAH HUJAN DI DAERAH TANGKAPAN AIR PROVINSI LAMPUNG - Manik, Tumiar Katarina (Bumi Lestari; Vol 10 No 2 (2010), 2010)
One important climate factor for tropical area is rainfall. Changes in rainfall pattern will cause numerous problems especially in agricultural activities and it could also lead to either flood or drought; problems which will not only affect agricultural activities but also socio-economic situation of broad community. Therefore, study of local climate variability focusing on rainfall related to the global warming is important. Time series analysis ( correlogram and periodogram) of daily rainfall was chosen to investigate the phenomena of global warming in local scale. Data (1974-2004) was collected from Sumberjaya, Air Hitam and Fajar Bulan; three stations located inside one of the important watershed in Lampung Province. From the correlogram, in general daily rainfall in this upland and forest area shows independency up to the year of 1990. No seasonal pattern could be an indicator that rains in this area are controlled more by local topography and land cover condition then by larger scale of climate system such as monsoon. After 1990 there were some weak sign of seasonal pattern. This could be interpreted as a sign that larger climate system started influence the local rainfall and as the global warming increases, it could be predicted that local rainfall pattern will be controlled more by the larger climate system. The periodogram shows that rainfall in this area has weak annual periodic. Data from Sumberjaya on 1990-1994 and 1999-2006 showed that annual periodic were getting stronger; a sign that larger climate system started dominating the area.
Keywords: correlogram; periodogram; rainfall pattern; time series